Open-heart transseptal transcatheter mitral valve implantation with mitral annular calcification. Issue 5 (November 2020) - Morita, Shohei; Takahashi, Shinya; Pernot, Mathieu; Leroux, Lionel; Labrousse, Louis
Abstract: Mitral valve replacement (MVR) using a prosthesis of transcatheter aortic valve implantation for mitral annular calcification (MAC) is an alternative procedure which is very different from a conventional MVR and is safe. Acceptable results including mortality and morbidity have been reported. We report the case of a male patient treated with this procedure. There was a risk of left ventricular rupture due to extensive decalcification, so we performed transcatheter mitral valve implantation (TMVI). Since he had a history of surgical aortic valve replacement (AVR), we chose open-heart transseptal approach so as not to interfere with the aortic prosthesis. TMVI has a risk of an iatrogenic left ventricular outflow tract (LVOT) obstruction. Using open-heart transseptal approach, we could easily check an anterior commissure of mitral annulus to prevent LVOT obstruction. <Learning objective: Transcatheter mitral valve implantation (TMVI) using a transcatheter aortic prosthesis is safe for mitral valve disease with mitral annular calcifications. This patient had a history of surgical aortic valve replacement, so we performed open-heart transseptal TMVI to prevent interference with the aortic prosthesis and the iatrogenic left ventricular outflow tract obstruction.>